KAJIAN PENEGAKAN HUKUM JUDI ONLINE DALAM PERSPEKTIF HUKUM DI INDONESIA - Komang edy Dharma Sapurta; Kadek Dedy Suryana (Universitas Mahendradatta, 2026)
The development of information technology, especially internet media technology, not only meets the needs of society for efficiency and convenience for those who want something practical, but also gives rise to new forms of crime. This crime is committed by utilizing technology such as computers and internet media as its mode of operation. Through the internet media, various types of crimes can occur, ranging from pornography to gambling crimes.